Expanded morphological description of the recently described Lycodon zayuensis (Serpentes: Colubridae) - Lyu, Bing; Li, Qinglian; Li, Ke; Li, Ling; Shu, Fu; Wu, Yayong; Guo, Peng (Zootaxa, 2022)
Lycodon is a species-rich genus that currently contains 72 named species. Lycodon zayuensis Jiang, Wang, Jin & Che, 2020, was described from Lower Chayu Town, Chayu County, Tibet, China, based on a single female holotype. During our recent field work, three additional specimens, including two females and one male, were collected and identified as L. zayuensis based on morphological comparison and the cytochrome b mitochondrial gene (1049 bp). Here, we provide an expanded description of this recently described species based on all known specimens.